Ophthalmology and Ethics in the COVID-19 Era - Prager, Kenneth M. (Am J Ophthalmol, 2021)
PURPOSE: The novel coronavirus, SARS-CoV-2 (COVID-19), has disrupted the practice of ophthalmology and threatens to forever alter how we care for our patients. Physicians across the country encounter unique clinical dilemmas daily. This paper presents a curated set of ethical dilemmas facing ophthalmologists both during and following the pandemic. DESIGN: Perspective. METHODS: Case presentations drawn from actual clinical scenarios were presented during a virtual ophthalmology grand rounds and discussed with the director of clinical ethics at Columbia University Irving Medical Center. RESULTS: It has become routine to expect an ophthalmologist to be involved in many levels of care for patients critically ill with COVID-19. Ophthalmology patients, even those with chronic, progressive conditions, are being triaged, and vision-saving interventions are being postponed. Four questions were applied to each scenario, allowing for ethical conclusions to be reached. The following questions were posed: what is the imminence and severity of the harm expected without intervention? What is the efficacy of the intervention under consideration? What are the risks of treatment for the patient? What are the risks of treating the patient for the health care team? CONCLUSIONS: During this pandemic and for months, perhaps years, to come, it is critical to reconsider the ethical principles underlying modern medicine and ophthalmic care as well as the ramifications of our decisions and actions.